Uncertainty assessments of structural loading due to first year ice based on the ISO standard by using Monte-Carlo simulation. (15th February 2020) - Sinsabvarodom, Chana; Chai, Wei; Leira, Bernt J.; Høyland, Knut V.; Naess, Arvid
Abstract: Sea ice is the major source of loading for structural design in cold regions. The intrinsic properties of sea ice are generally associated with high degrees of uncertainty due to ice growth taking place during different environmental conditions for different areas. The thickness, ice strength coefficient and flexural strength of sea ice are the parameters for the calculation of ice loads. The aim of the present paper is to investigate the uncertainties associated with the ice loads, which are acting on vertical and sloping structures as calculated by the formulations in the ISO 19906 standard. The effect of correlation between the key parameters is investigated by using the Nataf transformation model. Monte-Carlo simulation techniques are applied in order to assess the uncertainties associated with the global ice loads due to ice-structure interaction. It is found that for increasing values of the positive correlation between the sea ice properties, the uncertainties of the global ice forces will increase the fractile for both vertical and sloping structures approximately up to 40% and 60% from the case with zero correlation. Moreover, for sloping structures, higher values of the sloping angles imply increasing levels of uncertainty associated with the ice loads. Highlights: Monte-Carlo simulation techniques are applied in order to assess the uncertainties associated with the ice loads. Effects of correlation between flexural strength and ice thickness on uncertainty levels for ice loads are demonstrated. Higher slope inclination angles imply higher uncertainty levels for the horizontal ice loading. For vertical structures, levels of uncertainty for ice pressures versus correlation between strength and thickness are decreasing. For vertical structures, the uncertainty levels associated with the global ice forces exhibit an opposite trend as compared to the ice pressure.